A comprehensive examination of shielding and core influence through finite element analysis for the dynamic wireless charging magnetic coupler - Kantipudi V.V.S.R. Chowdary; Kundan Kumar; Byamakesh Nayak (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
This research paper investigates the influence of shielding and core materials on the performance of dynamic wireless charging (DWC) systems. A 2D model for finite element analysis (FEA) is developed to assess the flux density of coil structures within the DWC system, considering various combinations of shielding and core materials. Specifically, the study focuses on employing an aluminum shield and a ferrite core in the DWC system. Through the finite element analysis, the mutual inductance and efficiency of the DWC system are evaluated, with the simulations accounting for the presence of the aluminum shield and ferrite core to discern their impact on system performance. The FEA analysis is instrumental in determining the mutual inductance and power transferred under different scenarios, thus enabling technical evaluation. The research findings reveal the ramifications of using specific shielding and core materials on the performance of the DWC system, offering insights into the finest configurations for various applications. The novelty of this study lies in leveraging FEA analysis to comprehensively evaluate the influence of shielding and core materials on DWC system performance. As a result, this work presents valuable guidance for designing and configuring DWC systems tailored to specific applications. The insights provided pave the way for an enhanced understanding of DWC systems, ultimately fostering advancements in wireless charging technology.